Gut microbiota modulation via fecal microbiota transplantation mitigates hyperoxaluria and calcium oxalate crystal depositions induced by high oxalate diet - Lingyue An; Shujue Li; Zhenglin Chang; Min Lei; Zhican He; Peng Xu; Shike Zhang; Zheng Jiang; Muhammad Sarfaraz Iqbal; Xinyuan Sun; Hongxing Liu; Xiaolu Duan; et al. (Gut Microbes)
Hyperoxaluria, including primary and secondary hyperoxaluria, is a disorder characterized by increased urinary oxalate excretion and could lead to recurrent calcium oxalate kidney stones, nephrocalcinosis and eventually end stage renal disease. For secondary hyperoxaluria, high dietary oxalate (HDOx) or its precursors intake is a key reason. Recently, accumulated studies highlight the important role of gut microbiota in the regulation of oxalate homeostasis. However, the underlying mechanisms involving gut microbiota and metabolite disruptions in secondary hyperoxaluria remain poorly understood. Here, we investigated the therapeutic efficacy of fecal microbiota transplantation (FMT) sourced from healthy rats fed with standard pellet diet against urinary oxalate excretion, renal damage and calcium oxalate (CaOx) crystal depositions via using hyperoxaluria rat models. We observed dose-dependent increases in urinary oxalate excretion and CaOx crystal depositions due to hyperoxaluria, accompanied by significant reductions in gut microbiota diversity characterized by shifts in Ruminococcaceae_UCG-014 and Parasutterella composition. Metabolomic analysis validated these findings, revealing substantial decreases in key metabolites associated with these microbial groups. Transplanting microbes from healthy rats effectively reduced HDOx-induced urinary oxalate excretion and CaOx crystal depositions meanwhile restoring Ruminococcaceae_UCG-014 and Parasutterella populations and their associated metabolites. Furthermore, FMT treatment could significantly decrease the urinary oxalate excretion and CaOx crystal depositions in rat kidneys via, at least in part, upregulating the expressions of intestinal barrier proteins and oxalate transporters in the intestine. In conclusion, our study emphasizes the effectiveness of FMT in countering HDOx-induced hyperoxaluria by restoring gut microbiota and related metabolites. These findings provide insights on the complex connection between secondary hyperoxaluria caused by high dietary oxalate and disruptions in gut microbiota, offering promising avenues for targeted therapeutic strategies.